The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.32615/ps.2019.087
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of growth and photosynthesis in diverse cotton genotypes under hypoxia stress

Abstract: The objectives of the present study were to compare the dynamic of the growth and photosynthetic characteristics of cotton varieties contrasting in waterlogging (WL) tolerance when subjected to hypoxia stress. The growth of the WL-sensitive genotypes was notably inhibited by WL, mainly as a result of a significant reduction in the net photosynthesis (PN) after two days of hypoxia treatment; in the tolerant varieties, no significant changes in PN were observed until 8 d after hypoxia onset. The intercellular CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…The decrease in Fv/Fm was noted in more sensitive tomato and cucumber plants in our experiments. In agreement with our results, a decrease in Fv/Fm after waterlogging was also observed in rice [54,57], cucumber [56,58], tomato [59,60], wild tomato (Solanum habrochaites S.Knapp & D.M.Spooner) [61], Arabidopsis (Arabidopsis thaliana L.) [62], cotton [39], and pepper (Capsicum annuum L.) plants [63]. Barik et al [57] examined the reaction of tolerant and susceptible varieties of rice to submergence and observed that the latter exhibited a greater reduction in Fv/Fm parameters in comparison to tolerant varieties.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The decrease in Fv/Fm was noted in more sensitive tomato and cucumber plants in our experiments. In agreement with our results, a decrease in Fv/Fm after waterlogging was also observed in rice [54,57], cucumber [56,58], tomato [59,60], wild tomato (Solanum habrochaites S.Knapp & D.M.Spooner) [61], Arabidopsis (Arabidopsis thaliana L.) [62], cotton [39], and pepper (Capsicum annuum L.) plants [63]. Barik et al [57] examined the reaction of tolerant and susceptible varieties of rice to submergence and observed that the latter exhibited a greater reduction in Fv/Fm parameters in comparison to tolerant varieties.…”
Section: Discussionsupporting
confidence: 92%
“…Barik et al [57] examined the reaction of tolerant and susceptible varieties of rice to submergence and observed that the latter exhibited a greater reduction in Fv/Fm parameters in comparison to tolerant varieties. Similarly, in an experiment with cotton, the Fv/Fm parameter was stable in tolerant varieties and significantly decreased in sensitive varieties under hypoxia [39]. In the case of sorghum after waterlogging stress, the changes in Fv/Fm parameters were not significant, despite the observation of a substantial decrease in the Fv/F 0 parameter [64].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies showed that the net photosynthetic rate of waterlogging‐sensitive cotton significantly decreased at 2 days of hypoxia treatment (Pan et al 2019a, 2019b). In wheat, the plant height was reduced by 30% after hypoxia treatment for 8 days (Pan et al 2019a, 2019b).…”
Section: Discussionmentioning
confidence: 93%